Collaborating across sectors to provide early intervention for Aboriginal and Torres Strait Islander children with disability and their families: a qualitative study of provider perspectives. Issue 3 (3rd May 2020) - Green, Anna; Abbott, Penelope; Luckett, Tim; Davidson, Patricia Mary; Delaney, John; Delaney, Patricia; Gunasekera, Hasantha; DiGiacomo, Michelle
ABSTRACT: Aboriginal and Torres Strait Islander children experience a higher prevalence of disability than other Australian children. Early intervention from across the health, education, and social service sectors is vital for improving outcomes, but families face lack of coordination between services. This study aimed to inform improvements in service access for families of urban-dwelling Aboriginal children with disability through exploring providers' perceptions of factors that influenced working together across sectors. Semi-structured interviews were conducted. Data analysis was informed by the general inductive approach and the Collaborative Practice to Enhance Patient Care Outcomes framework. Twenty-four providers participated. Interprofessional collaborative practice was influenced by interdependent interactional and organizational factors. Interactional factors fit within one of two dimensions: the ability of providers to share common goals and vision within a complex cross-sector service landscape, and influence of interpersonal relationships on their sense of belonging working in a cross-cultural space. Organizational factors also fit within one of two dimensions: the influence of governance in relation to its role in coordination and unlocking the strength of schools as service settings, and the need to formalize processes for effective interprofessional communication. Interprofessional collaborative practice was managed within the context of systemic factors relating to policy and funding. These findings demonstrate the complex interplay of factors related to the cross-sector involvement of providers in early intervention service provision. Consideration of these factors is required to facilitate collaborative cross-sector responses to improve service access for Aboriginal families. Abbreviations: WHO: world health organization; ACCHS: aboriginal community controlled health service; GP: general practitioner; NDIS: national disability insurance scheme